2001
DOI: 10.1007/s002400100176
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine as a preventive agent in experimental renal ischemia-reperfusion injury

Abstract: Reactive oxygen species generated during the reperfusion of ischemic kidney, as well as any other tissue, cause lipid peroxidation damaging the cell membrane. The aim of this study was to investigate the effect of carnitine in reperfusion injury of the kidney. Male albino rabbits were subjected to unilateral renal 1-h warm ischemia followed by 15 min of reperfusion. Group I (n = 9): control group received 3 cc of isotonic saline solution and group II (n = 9): carnitine group received 100 mg/kg of carnitine. Bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 0 publications
1
25
0
2
Order By: Relevance
“…In many studies serum and/or tissue MDA levels were shown as increased. 19,20,22,[44][45][46][47] In our study, serum creatinine and tissue MDA levels were significantly higher in AIR group than other groups. Also there was a positive correlation between serum creatinine and tissue MDA levels and between creatinine values and TSHD.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…In many studies serum and/or tissue MDA levels were shown as increased. 19,20,22,[44][45][46][47] In our study, serum creatinine and tissue MDA levels were significantly higher in AIR group than other groups. Also there was a positive correlation between serum creatinine and tissue MDA levels and between creatinine values and TSHD.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore possible histopathological changes after infrarenal aortic occlusion and reperfusion decreased in a dose-related fashion by carnitine administration. Ergun et al 19 in rabbits and Onal et al 21 in rats showed that in IR damage developed by clamping of renal arteries carnitine decreased histopathological changes in kidneys. In similar models, Mister et al showed that carnitine improved tubular lesions developed by renal IR damage in their studies on rat.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In previous studies, LC has been shown to have antioxidant effects against oxidative damage in different organs or tissues, including the kidney (Aydogdu et al, 2006;Chang et al, 2002). It has been demonstrated that LC administration inhibits both serum and kidney tissue MDA formation in response to renal ischaemia-reperfusion injury (Ergün et al, 2001). Carnitine supplementation has been found to enhance the activities of antioxidant enzymes, such as SOD, CAT and GPx, and decrease the MDA concentration in kidney tissues of 24-month-old rats .…”
Section: Discussionmentioning
confidence: 98%